Anaplastic thyroid cancer: a comprehensive review of novel therapy. Issue 3 (March 2011) - Kojic, Stefan L; Strugnell, Scott S; Wiseman, Sam M
Thyroid carcinomas are the most common cancer of the human endocrine system and are typically classified as papillary, follicular, anaplastic or medullary carcinomas. Although epidemiological studies have suggested an increased incidence of anaplastic thyroid carcinomas (ATCs) worldwide, there has been little evidence to suggest that, with current treatment, there has been any improvement in patient survival over the past two decades. Anaplastic thyroid carcinoma is one of the most aggressive human malignancies and is responsible for a disproportionate number of thyroid cancer-related deaths. Currently, available therapy for ATCs includes: chemotherapy, radiotherapy and surgery. Due to the poor treatment outcomes for individuals diagnosed with ATCs who undergo conventional therapy, novel therapeutic strategies for the treatment of ATCs are urgently needed. In this article, we review the existing management of ATCs, with a focus on novel molecular-targeted approaches as described in preclinical studies and in early human clinical trials.